How to optimize dust pollution control in opencast coal mines: Analysis of a joint social regulation model based on evolutionary game theory. - Xu Lian; Wensheng Wang; Jianmin Zhang (PLoS ONE)
The carbon peaking and carbon neutrality goals drive innovation in pollution governance systems, unleashing the potential of social supervisory forces to achieve coordinated governance by multiple stakeholders. In order to improve dust pollution control in opencast coal mines, this study combines prospect theory with evolutionary game theory, analyzing the evolutionary game process of coordinated governance activities of coal mining enterprises, local regulators, and social camps in the management of dust pollution against the backdrop of national supervisions. The research indicates that the perceived value of dust pollution has a significant impact on the strategic choices of the three agents involved in the game. Coal mining enterprises tend to be risk averse, and by reducing the cost of dust pollution control and increasing the additional benefits of pollution control, it can promote pollution control behavior by coal mining enterprises. Local regulators are also risk averse, but not sensitive to risk benefits. Strengthening pollution subsidy incentives and environmental fines can help promote dust pollution control behavior by coal mining enterprises. However, increasing the strength of the rewards strategy is not conducive to local regulators' own regulatory responsibilities, and environmental fines have limited binding effects. The strategic choices of social camps' supervision have a restrictive effect on the strategic choices of coal mining enterprises and local regulators, promoting the evolution of equilibrium results in the direction of maximizing social benefits. When coal mining enterprises actively governance pollution, local regulators strictly regulated, and social camps do not monitor, the system reaches its optimal equilibrium state. The research results clarify the mechanism and specific effects of social supervision of opencast coal mine dust pollution control, guide the participation of the public in dust pollution control, and regulate the behavior strategies of coal mining enterprises and local regulators, providing the scientific basis for management.